Advanced microstructural substrate detection in pre-hypertrophic HCM and its relationship to arrhythmogenesis; a hybrid CMR-ECG-Imaging study. (3rd October 2022) - Joy, G; Webber, M; Kelly, C I; Pierce, I; Teh, I; Schneider, J; Nguyen, C; Kellman, P; Orini, M; Lambiase, P; Rudy, Y; Captur, G; et al.
Abstract: Background: Hypertrophic cardiomyopathy is defined in three domains; clinically by unexplained hypertrophy, genetically by sarcomeric gene mutations and histologically by disarray, small vessel disease and fibrosis. Both ischaemia and myocyte disarray have been implicated in arrhythmogenesis and sudden cardiac death but whether disarray occurs before hypertrophy and its relationship to ischaemia is unknown. Diffusion-tensor CMR, perfusion mapping & ECG Imaging (ECGI) can measure disarray, ischaemia and electrical aberrance respectively in vivo. We aimed to investigate these in genotype positive (G+) subjects without hypertrophy (LVH−) to identify further subclinical manifestations of gene expression and whether these relate to ventricular arrhythmia formation. Methods: Diffusion-tensor CMR (3-Tesla) using a motion-compensated spin-echo sequence was acquired in 3 short-axis slices. Quantitative adenosine stress perfusion mapping was performed using standard clinical protocols. A novel ECGI vest, containing 256 unipolar electrodes acquired a 5-minute recording of body-surface potentials to quantify conduction and repolarisation dynamics intervals. Results: ECGI/CMR was performed on 68 mutation carriers from 64 families and 24 age sex and ethnicity matched healthy controls. Of the mutation carriers, median age was 33 (24–41 years), 57% (39) were female, and 79% (54) were white. Mutations were 39 (57%) MYBPC3, 19 (28%) MYH7, 1 (1%) MYL2 and 9 (12%) were thin filament/non-sarcomeric mutations. There was no significant difference in ejection fraction or LV mass, however G+LVH− had a higher maximum wall thickness (9 (9–10) vs 8 (7–9) mm p=0.003). Compared to healthy volunteers, G+LVH− individuals had more perfusion defects (18/64 (30%) vs 0, p=0.004), lower Fractional Anisotropy (FA) (suggestive of more disarray) (0.32±0.02 vs 0.34±0.02, p<0.0001) and more prolonged Activation–Recovery Intervals (ARI, a surrogate for action potential duration (259±40 vs 240±31 ms, p=0.03). In G+LVH−, patients with perfusion defects had more prolonged ARI (263 (248 vs 292) vs 246 (225–283) ms, p=0.03) and lower FA suggestive of more disarray (0.32±0.2 vs 0.31±0.1, p=0.04). Conclusion: Ischaemia, myocyte disarray and electrical abnormalities occur even in the absence of hypertrophy in HCM. These abnormalities associate to form a complex a clinical phenotype. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): British Heart FoundationBarts Charity